數學學術素養：數學話語在課程與教學上的應用 Mathematics Academic Literacy: The Application of Mathematical Discourse in Curriculum and Teaching - 陳嘉皇 Chia-Huang Chen (Higher Education Foundation, 2021)
發展數學語言是向學生教授數學的重要層面，此過程會在整個數學教育中持續 進行。就數學語言而言，使用詞彙解釋、證明和進行數學溝通的能力對於整體數學能力的發展至關重要，數學詞彙的理解使人們可以使用概念，所以在語言領域進行數學教學勢在必行。本文擬透過Moschkovich提出的數學專業素養內涵介紹，以數學話語連結數學能力和實踐，闡述數學話語的特徵和數學詞彙的類型，提供數學話語教學的流程與實例，希望藉此提供教師在未來實施數學語言領域教學之參考依據。 The development of mathematics language is an important aspect of teaching mathematics to students, and this process will continue throughout the mathematics education. As far as mathematical language is concerned, the ability to use vocabulary to explain, prove, and communicate mathematically is essential to the development of overall mathematical ability. The understanding of mathematical vocabulary allows people to use concepts, so it is imperative to carry out mathematical teaching in the field of language. This article intends to introduce the Moschkovich's connotation of mathematical profession literacy, connect mathematical ability and practice with mathematical discourse, explain the characteristics of mathematical discourse and the types of mathematical vocabulary, provide the process and examples of mathematical discourse teaching, and hope to provide teachers with the teaching of mathematics in the future reference basis.